Subscription Page (Quarterly Journal of Economics, 2014)
Journal Article Subscription Page Get access The Quarterly Journal of Economics, Volume 129, Issue 1, February 2014, Page i3, https://doi.org/10.1093/qje/qjt039 Published: 11 January 2014